An Investigation Release and Rheological Properties of Miconazole Nitrate from Emulgel - A.Sabri, Lubna; T. Sulayman, Hala; I. Khalil, Yehia (Iraqi Journal of Pharmaceutical Sciences, 2017)
In this study miconazole nitrate was formulated as topically applied emulgel; different formulas were prepared using sodium carboxymethylcellulose (SCMC) and carboxypolymethylene (carbomer 941) as gelling agents. The influence of type of gelling agent and concentration of both oil phase and emulsifying agent on drug release was studied and compared with commercially available miconazole nitrate cream (MecozalenÂ®). The results of in vitro release showed that SCMC emulgel bases gave better release than carbomer 941 bases and the release of drug increase from both bases as a function of increasing the concentration of emulisifying agent. The oil phase had retardation effect when its concentration increased. The formula which showed the highest drug release was chosen to evaluate its rheology and its stability .The rheological behavior of selected formula showed share-thinning flow indicating structural break down of intermolecular interaction between polymeric chains. Moreover, the expiration date of the selected emulgel was found to be 1.7 year as well as their physical properties like, color, pH and consistency remains constant along storage time. Keywords: emulgel, carbomer, miconazole nitrate, carboxymethyl cellulose.